On the Guard of the Truth of History - S. N. Kovalev (Евразийская интеграция: экономика, право, политика, 2021)
The article focuses on the continuing relevance of research in the field of military history for the joint solution of problems of cooperation and security from the Atlantic to the Pacific Ocean within the framework of the Greater Eurasian Partnership. The historical path of the Research Institute (military history) the Military Academy of the General Staff of the Armed Forces of the Russian Federation is described consistently stopping at the stages of its activity. The information about the formation of the Institute, its structure, tasks, and the heads of the Institute is presented. The article provides an overview of fundamental works, research works performed by the Institute’s staff, information about famous scientists, laureates of various awards. The contribution of the Institute’s staff to the implementation of the state programs “Patriotic education of citizens of the Russian Federation” is shown. The range of tasks solved in the interests of federal state authorities and subjects of the Russian Federation, military administration bodies is characterized. The contribution of the Institute to the provision of the educational process of military educational institutions, the holding of international Olympiads of cadets of military educational organizations of higher education of the CIS member states on military history is observed. An overview of the international activities of the Institute within the framework of the International Commission of Military History, with the CIS countries, the CSTO, the EAEU is given. The role of the Institute in solving the problems of scientific information in the Armed Forces of the Russian Federation in terms of the history of wars and military art, in countering attempts to falsify and distort military history that harm the interests of the Russian Federation is shown. It is emphasized that the main content of the Institute’s activities is the need to preserve the truth about the victory of the Soviet multinational people in the Great Patriotic War, strengthen cooperation with relevant organizations and structures of the states of the Eurasian Economic Union, the Collective Security Treaty Organization, the Union State.